A simple method for preparing Ag-Au composite nanostructures with high SERS activity

By depositing silver film on a single-pass anodized oxidized phenotype template and performing high-temperature domain-limited spheroidization treatment, combining the substitution reaction of gold ion solution, Ag-Au composite nano-period structure was prepared, which solved the problem of insufficient signal uniformity and batch repeatability of existing SERS detection substrates, and achieved high SERS activity and stability.

CN111041427BActive Publication Date: 2025-02-28NANTONG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201911181579.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2019-11-27
Publication Date
2025-02-28
Estimated Expiration
2039-11-27

AI Technical Summary

Technical Problem

The existing SERS detection substrates have shortcomings in signal uniformity and batch repeatability, which limits their commercialization.

Method used

A simple preparation method is adopted to prepare an Ag-Au composite nano-period structure by depositing silver film on a single-pass anodized aluminum template and performing high-temperature domain-limited spheroidization treatment to form a silver nanoparticle array substrate, and then performing a substitution reaction in a gold ion solution.

Benefits of technology

The preparation of Ag-Au composite nano-period structure with high SERS activity has achieved uniform structure, high detection sensitivity and repeatability, is suitable for a variety of probe molecules, and the SERS performance remains stable within 30 days.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111041427B_ABST
    Figure CN111041427B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of nanomaterials, and discloses a simple preparation method of a Ag-Au composite nano-periodic structure with high SERS activity, comprising the following steps: evaporating a layer of silver film on the surface of a single-pass anodized aluminum template channel, wherein the silver film forms uniformly arranged silver nanoparticles in the channel through a high-temperature confined spheroidization process; using Au 1 The solution undergoes a substitution reaction to obtain an Ag-Au composite nanoperiodic structure, which is used for SERS activity detection of a variety of probe molecules. Compared with the prior art, this method overcomes the problem of poor repeatability of SERS signals of traditional nanoparticle colloids, realizes the controllable preparation of large-area Ag-Au composite nanoperiodic structures and their high repeatability and high activity detection of SERS, greatly reduces the preparation cost of periodic nanostructures, and is suitable for mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanomaterials, and in particular to a simple preparation method of an Ag-Au composite nano periodic structure with high SERS activity. Background Art

[0002] Surface-enhanced Raman scattering (SERS) refers to the phenomenon that when the molecules being measured are adsorbed on a rough metal surface, their Raman scattering signals are abnormally amplified. This technology is an emerging surface detection technology developed based on Raman spectroscopy, and has now reached the level of single-molecule detection. In addition to relying on instrument accuracy, the improvement of SERS detection level also requires the preparation of a detection substrate with high sensitivity and good repeatability. Research results show that the activity of SERS substrates mainly comes from the electromagnetic field enhancement on the substrate surface, especially the ultra-strong electromagnetic field caused by the local surface plasmon resonance (LSPR) characteristics of nanogaps or nanotips, which is the key factor in achieving high-sensitivity detection.

[0003] A large number of studies have shown that the SERS activity of metallic silver is higher than that of gold, but its stability is not as good as that of gold. In particular, the gold nanostar structure, which has received increasing attention in recent years, has greatly improved its SERS activity and has the advantage of biocompatibility, and has been used in the detection of biological proteins. However, liquid phase synthesis is currently commonly used to prepare gold nanostars or gold nanopolyhedron sols, which are then transferred to a solid substrate by interfacial assembly for adsorption of molecules to be tested; or liquid phase is directly used for in situ SERS analysis. The gold nanostructures prepared in this way are relatively uniform and controllable, and can ensure a certain detection sensitivity, but their signal uniformity and batch repeatability need to be improved, which also limits the commercialization of the substrate. In addition, combining the advantages of gold and silver, bimetallic composite nanomaterials have gradually received attention, among which the most commonly reported is the core-shell structure, which is also prepared by liquid phase synthesis. The experimental repeatability and signal uniformity need further study.

[0004] Experiments have shown that the preparation of periodic solid-state metal nanostructures is an effective supplement to the defects of the liquid phase method, especially the imprint transfer or in-situ deposition based on periodic templates. Its uniform LSPR advantage has been widely used in the field of SERS detection. This technology has strong operability and high controllability, and the signal uniformity and batch reproducibility have been greatly enhanced. However, due to the limitation of template size, obtaining nanogaps or nanotips with high SERS activity usually requires high-end precision equipment and is not universal.

[0005] In summary, there is an urgent need to develop a solid-state SERS detection substrate with uniform surface nanostructure, which can fully utilize the advantages of bimetallic composite materials to achieve high-sensitivity and high-repeatability detection of SERS signals and achieve the goal of low-cost commercialization. Summary of the invention

[0006] In view of this, the purpose of the present invention is to provide a simple preparation method of Ag-Au composite nano-periodic structure with high SERS activity. The method provided by the present invention has low preparation cost, uniform and controllable structure, and wide applicability.

[0007] The present invention provides a simple preparation method of an Ag-Au composite nano-periodic structure with high SERS activity, comprising the following steps:

[0008] Step 1, depositing a layer of silver film on the surface of the pores of the single-pass anodized aluminum template;

[0009] Step 2, subjecting the metal film to a high-temperature confined spheroidization process to form discontinuous silver nanoparticles at the bottom of the pores and on the pore walls, thereby obtaining a template-based silver nanoparticle array substrate;

[0010] Step 3, immersing the template-based silver nanoparticle array substrate obtained in step 2 in a gold ion solution for different periods of time to obtain an Ag-Au composite nanoperiodic structure;

[0011] Step 4, immersing the Ag-Au composite nano-periodic structure obtained in step 3 in different molecular solutions to be tested, taking it out after 30 minutes, rinsing it with ultrapure water, and blowing it dry with nitrogen to obtain a sample to be tested.

[0012] Preferably, the pore size of the single-pass anodized aluminum template is 200-450 nm; the pore depth is 300-500 nm.

[0013] Preferably, the thickness of the silver film is 30-40 nm.

[0014] Preferably, the deposition method in step 1 is electron beam evaporation thermal deposition.

[0015] Preferably, the temperature of the high temperature confined spheroidization process in step 2 is 200° C. to 400° C., and the time is 1 h to 2 h.

[0016] Preferably, the gold ion solution in step 3 is Au 1 Solution; the soaking time is 5min or 15min.

[0017] Preferably, Au 1The solution is a freshly prepared solution. The specific preparation process is: add 40 mg NaBr to 12 ml of 1 mM chloroauric acid solution, shake to dissolve the NaBr; then, continuously add 121 μl of 0.1 M ascorbic acid solution during the shaking process to obtain colorless Au 1 Solution.

[0018] Preferably, the molecules to be detected in step 4 include Malachite Green (MG), Rhodamine 6G (R6G), Methylene Blue (MB) and 6-Mercaptopurine (6-MP).

[0019] Compared with the prior art, the present invention has the following advantages and effects:

[0020] (1) The present invention can realize the one-step preparation of large-area uniform Ag-Au composite nano-periodic structures. The confined spheroidization process enables the silver film deposited in the template pores to be spheroidized into nanoparticles in situ at one time, providing uniform reaction conditions for subsequent substitution reactions. This scheme effectively supplements the uncontrollability of preparing metal composite nanostructures by liquid phase synthesis.

[0021] (2) The SERS activity of the Ag-Au composite nanoperiodic structure provided by the present invention is applicable to a variety of probe molecules, and the SERS performance is stable and reliable, and the detection activity for a variety of molecules can be maintained for at least 30 days, which is significantly better than the pure silver or pure gold nanostructures reported previously. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the scanning electron microscope characterization result of the Ag-Au composite nanoperiodic structure obtained with a substitution reaction time of 5 minutes.

[0023] Figure 2 This is the scanning electron microscope characterization result of the Ag-Au composite nanoperiodic structure obtained with a substitution reaction time of 15 minutes.

[0024] Figure 3 This is the result of characterizing the SERS activity of the Ag-Au composite nano-periodic structure prepared in Example 1 of the present invention to different molecules.

[0025] Figure 4 These are the results of characterizing the SERS sensitivity and stability of the Ag-Au composite nano-periodic structure prepared in Example 2 of the present invention to different molecules after long-term storage.

[0026] Figure 5 It is a schematic diagram of the SERS spectrum captured by randomly selecting 15 points on the sample surface in an embodiment of the present invention. DETAILED DESCRIPTION

[0027] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0028] The present invention provides a simple preparation method of an Ag-Au composite nano-periodic structure with high SERS activity, comprising the following steps:

[0029] Step 1, depositing a layer of silver film on the surface of the pores of the single-pass anodized aluminum template;

[0030] Step 2, subjecting the metal film to a high-temperature confined spheroidization process to form discontinuous silver nanoparticles at the bottom of the pores and on the pore walls, thereby obtaining a template-based silver nanoparticle array substrate;

[0031] Step 3, immersing the template-based silver nanoparticle array substrate obtained in step 2 in a gold ion solution for different periods of time to obtain an Ag-Au composite nanoperiodic structure;

[0032] Step 4, immersing the Ag-Au composite nano-periodic structure obtained in step 3 in different molecular solutions to be tested, taking it out after 30 minutes, rinsing it with ultrapure water, and blowing it dry with nitrogen to obtain a sample to be tested.

[0033] Specifically, the present invention firstly evaporates a layer of silver film on the pore surface of the single-pass anodized aluminum template. In the present invention, the single-pass anodized aluminum template preferably adopts a single-pass anodized aluminum template with a pore size of 200 to 450 nm; the pore depth is 300 to 500 nm. The thickness of the deposited silver film is preferably 30 to 40 nm. The deposition method is preferably electron beam evaporation thermal deposition.

[0034] After the silver film is evaporated on the surface of the single-pass anodized aluminum template channel, a high-temperature confined spheroidization process is performed to form silver nanoparticles at the bottom of the channel. In the present invention, the temperature of the high-temperature confined spheroidization process is preferably 200°C to 400°C, and the time is 1h to 2h. Under the temperature and time conditions provided by the present invention, the silver nanoparticles after final spheroidization have a regular morphology and high surface smoothness.

[0035] After uniform silver nanoparticles are formed at the bottom of the pores, a Ag-Au composite nanoperiodic structure is obtained through a substitution reaction. The gold ion solution used for the substitution reaction in the present invention is Au 1 The different reaction times will produce Ag-Au composite nanostructures with different morphologies. The present invention shows the results of substitution reaction times of 5 min and 15 min. 1The solution is a freshly prepared solution. The specific preparation process is: add 40 mg NaBr to 12 ml of 1 mM chloroauric acid solution, shake to dissolve the NaBr; then, continuously add 121 μl of 0.1 M ascorbic acid solution during the shaking process to obtain colorless Au 1 The detection molecules of the present invention include 6-mercaptopurine (6-MP), methylene blue (MB), rhodamine 6G (R6G) and malachite green (MG).

[0036] In order to further understand the present invention, the method provided by the present invention is described in detail below in conjunction with embodiments, and the protection scope of the present invention is not limited by the following embodiments.

[0037] Example 1

[0038] In this embodiment, a single-pass anodized aluminum template with a pore size of 450 nm and a pore depth of 500 nm was selected to prepare an initial silver nanoparticle array. The thickness of the silver film deposition was 35 nm, the spheroidization temperature was 400° C., the spheroidization time was 2 h, and a Ag-Au composite nanoperiodic structure was obtained after a 5-minute substitution reaction.

[0039] The specific steps are as follows:

[0040] Firstly, a 35nm silver film was deposited on the surface of the pores of the single-pass anodized aluminum template, and then discontinuous silver nanoparticles were formed on the bottom and wall of the pores through a high-temperature confined spheroidization process to obtain a template-based silver nanoparticle array substrate; the obtained template-based silver nanoparticle array substrate was immersed in a gold ion solution for reaction for 5 minutes, and then taken out and washed with ultrapure water and dried by electric heating to obtain a Ag-Au composite nanoperiodic structure; finally, the prepared Ag-Au composite nanoperiodic structure was immersed in 6-mercaptopurine (6-MP), methylene blue (MB), rhodamine 6G (R6G) and malachite green (MG) molecular solutions, with a concentration of 10 - 5 M, take it out after 30 minutes, rinse it with ultrapure water, blow it dry with nitrogen, and obtain the sample to be tested.

[0041] Example 2

[0042] The difference between Example 2 and Example 1 is that the substitution reaction time is 15 min, the concentration of the four detection molecules is 10 -6 M.

[0043] The specific steps are as follows:

[0044] Firstly, a 35nm silver film was deposited on the surface of the pores of the single-pass anodized aluminum template, and then discontinuous silver nanoparticles were formed on the bottom and wall of the pores through a high-temperature confined spheroidization process to obtain a template-based silver nanoparticle array substrate; the obtained template-based silver nanoparticle array substrate was immersed in a gold ion solution for reaction for 15 minutes, and then taken out and washed with ultrapure water and dried by electric heating to obtain a Ag-Au composite nanoperiodic structure; finally, after being stored for 30 days, the prepared Ag-Au composite nanoperiodic structure was immersed in different concentrations of 6-mercaptopurine (6-MP) and methylene blue (MB) solutions, and concentration gradient analysis was performed; in addition, signal stability analysis was performed on rhodamine 6G (R6G) and malachite green (MG) molecules, with concentrations of 10 -5 M. All solutions were taken out after immersion for 30 min, rinsed with ultrapure water, and dried with nitrogen to obtain the samples to be tested.

[0045] Test Example 1: Scanning Electron Microscope Characterization and Energy Spectrum Analysis

[0046] The Ag-Au composite nanostructures obtained in Example 1 and Example 2 were characterized by scanning electron microscopy and energy spectrum analysis. The results were as follows: Figure 1 and Figure 2 As shown. Among them, Figure 1 (a) and (b) are scanning electron micrographs of Ag-Au composite nanostructures after 5 min of reaction. (b) is an enlarged view of the dotted circle in (a). Figure 1 (c) is the energy spectrum analysis result of the dotted circle in (a). Figure 2 (a) and (b) are scanning electron micrographs of Ag-Au composite nanostructures after 15 min of reaction. (b) is an enlarged view of the dotted circle in (a). Figure 2 (c) Figure 2 (a) The energy spectrum analysis results of the dotted circle part. It can be seen from the above two figures that when the substitution reaction time is short, only a small amount of silver nanoparticles on the pore wall react with the gold ion solution, and the reduced gold nanoparticles are in the nucleation stage and have not yet grown into polyhedrons; the composition analysis results show that at this time, the atomic percentages of silver and gold are 8.30% and 1.04%, respectively. When the reaction time is extended to 15 minutes, the nucleated gold particles continue to grow along the crystal plane and become gold polyhedrons, such as Figure 2 As shown in (a), the nanostructure is more dense, which is more conducive to the enhancement of the local electromagnetic field; the composition analysis results show that the atomic percentages of silver and gold are 5.24% and 27.03% respectively.

[0047] Test Example 2: SERS application analysis of four probe molecules

[0048] The four molecules of MG, R6G, MB and 6-MP were used as target analytes, and the Ag-Au composite nanostructures prepared in Example 1 and Example 2 were used as SERS detection substrates. The SERS signal analysis of the four molecules was performed respectively. The results are shown in FIG. Figure 3 , Figure 4 and Figure 5 As shown. Among them, Figure 3 The Ag-Au composite nanostructure obtained in Example 1 was used as the SERS substrate, and signal detection tests were performed on four molecules, 6-MP, MB, R6G and MG, with the detection concentrations of 10 -5 M. It can be seen from the SERS spectrum that the nanostructure prepared by the scheme of the present invention not only has a good signal detection ability for dye molecules with large scattering cross sections (MB, R6G, MG), but also has good activity for drug molecules 6-MP with a small scattering cross section, indicating that the scheme is feasible and effective.

[0049] Figure 4 The Ag-Au composite nanostructure obtained in Example 2 was used as the SERS detection substrate, and the concentration gradient of the above 6-MP and MB molecules was analyzed. The SERS sensitivity of the substrate after long-term storage was characterized. The results are as follows: Figure 4 (a) and (b). In addition, the repeatability of the SERS signals of R6G and MG molecules was analyzed. That is, after the samples were stored for 30 days, different positions on the sample surface were randomly selected to capture the signals. The uniformity of the substrate structure and the stability of the SERS activity were determined from the signal repeatability. The probe molecule concentration was selected as 10 -5 M, the results are as follows Figure 5 (a) and (b). Figure 4 It can be seen that the SERS substrate obtained by the present invention still has the ability to detect low concentrations after long-term storage. -8 At the M concentration, obvious characteristic peaks were still detected; Figure 5 The SERS spectrum is captured at 15 randomly selected points on the sample surface. From the waterfall plot, it can be seen that the Raman spectrum peaks at different sites are consistent, the peak intensity fluctuation is not obvious, and the relative standard deviation of the Raman intensity is less than 15%, indicating that the substrate obtained by the present invention is a reliable substrate with low-cost commercialization potential.

Claims

1. A simple method for preparing Ag-Au composite nano-periodic structure with high SERS activity, characterized in that: The steps include: Step 1, depositing a layer of silver film on the surface of the pores of the single-pass anodized aluminum template; Step 2, subjecting the silver film to a high-temperature confined spheroidization process to form discontinuous silver nanoparticles at the bottom of the pores and on the pore walls, thereby obtaining a template-based silver nanoparticle array substrate; Step 3, immersing the template-based silver nanoparticle array substrate obtained in step 2 in a gold ion solution for different periods of time to obtain an Ag-Au composite nanoperiodic structure; Step 4, immersing the Ag-Au composite nano-periodic structure obtained in step 3 in different molecular solutions to be tested, taking it out after 30 minutes, rinsing it with ultrapure water, and drying it with nitrogen to obtain a sample to be tested; The pore size of the single-pass anodized aluminum template is 200-450 nm; the pore depth is 300-500 nm; The gold ion solution is Au 1 Solution; The soaking time in step 3 is 5 min or 15 min; The Au 1 The solution is a freshly prepared solution. The specific preparation process is: add 40 mg NaBr to 12 ml of 1 mM chloroauric acid solution, shake to dissolve the NaBr; then, continuously add 121 μl of 0.1 M ascorbic acid solution during the shaking process to obtain colorless Au 1 Solution; The thickness of the silver film is 30 to 40 nm; The temperature of the high temperature confined spheroidization process in step 2 is 200° C. to 400° C., and the time is 1 h to 2 h.

2. The method for preparing a Ag-Au composite nano-periodic structure with high SERS activity according to claim 1, characterized in that: The deposition method in step 1 is electron beam evaporation thermal deposition.

3. The simple preparation method of a Ag-Au composite nano-periodic structure with high SERS activity according to claim 1, characterized in that: In step 4, the molecule to be detected includes one of 6-mercaptopurine (6-MP), methylene blue (MB), rhodamine 6G (Rhodamine 6G, R6G) and malachite green (MG).

Citation Information

Patent Citations

  • Method for preparing cauliflower nano gold-silver alloy with surface-enhanced Raman scattering activity

    CN101786170A

  • Gold nanoparticle-silver nano-semisphere array as well as preparation method and application thereof

    CN103447523A

  • Ordered nanostructured precious metal array, and preparation method and use thereof

    CN104977289A

  • Preparation method for aqueous phase solutions of monovalent gold complex ions (AuBr2<->) controllable in stability and preparation method for gold-silver alloy nanoparticles

    CN105642908A

  • Preparation method for SERS substrate of gold-silver composite nanometer particles

    CN105928924A